SUSTAINABILITY PERFORMANCE IN SMES: THE ROLE OF EMA AND RESILIENCE - Indah Yani; Dara Alifa Fajriati Thamrin (International Journal of Accounting, Management, Economics and Social Sciences (IJAMESC), 2026)
This paper examines how Environmental Management Accounting (EMA) can influence sustainability performance (SP), with strategic resilience (SR) serving as a mediating factor. Data were collected using a quantitative method, by surveying 127 small and medium-sized enterprises (SMEs) and focusing on the top management of the company that was involved in making strategic decisions. Partial Least Squares Structural Equation Modeling (PLS-SEM) was used to analyze the data. The results indicate that the positive and significant impact of EMA is on sustainability performance and strategic resilience. Moreover, strategic resilience has a positive impact on the sustainability performance and partially mediates the relationship between the EMA and SP. These findings show that although EMA can give the necessary environmental information, its ability to create sustainability performance relies on the ability of the organization to absorb, adapt, and transform the information into strategic action. This research is a contribution to the body of literature because it refutes the existing hypothesis that better sustainability performance is an automatic consequence of environmental information. Rather, it shows that the power of EMA is in its combination with the organizational capabilities, in particular, strategic resilience. The implications of the findings on SMEs are also practical in the sense that it is important that internal capabilities should be enhanced in order to maximize the utilization of environmental information in coming up with sustainable results.